Process Improvement Model based on Lean Manufacturing and Kaizen to Increase Machine Availability at a Plastics Company - Caso-Murillo, N. (2023)
The case study is a company that produces and sells plastic containers. Through a production time assessment, the low availability of injection machines was identified as the mam problem. The availability rate for these machines was set at 80.19%, which represented a relevant issue since the worldwide standard is 90%. These low availability rates are mainly due to machine breakdowns, representing 9.87% in lost revenue for the company. To improve machine availability, this study proposed an improvement model combining Lean Manufacturing tools with Kaizen, which refers to continuous process improvement. The model is also integrated with Ergonomics concepts aimed at improving working conditions for operators. Hence, if improvements are achieved regarding human capital, machine availability will also improve. Within this context, the proposed model was piloted at the company, increasing machine availability by 6.8%, reducing lost revenue by 3.9%, and increasing company profits by 13.12%.